2013
DOI: 10.1109/ted.2013.2281397
|View full text |Cite
|
Sign up to set email alerts
|

Performance Dependence on Width-to-Length Ratio of Si Cap/SiGe Channel MOSFETs

Abstract: This paper measures the n-and p-MOSFETs fabricated through 65-nm high-k/metal gate CMOSFET process flow. The [110] channels of the Si cap on SiGe with different width (W ) and length (L) ratios were compared with Si-only channels. The results show that a high W-L ratio in the [110] n-channel can alleviate the degradation of biaxial compressive stress. Meanwhile, a low W-L ratio in the p-channel can improve the performance; however, the ratio should at least be below two in this paper. The dominance of the long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…To find out the relationship between the width and length of CMOS, we should first find out the relationship of the ratio between each N-channel and P-channel. After experiment, the numerical value of the dimension interference can be calculated, which suggests that the higher value of Width makes degradation in P-channel, and the lower value of Width leads to enhancement [8]. It also observed that a shift of Threshold Voltage exists while changing the dimensions.…”
Section: Optimization Directionmentioning
confidence: 96%
See 1 more Smart Citation
“…To find out the relationship between the width and length of CMOS, we should first find out the relationship of the ratio between each N-channel and P-channel. After experiment, the numerical value of the dimension interference can be calculated, which suggests that the higher value of Width makes degradation in P-channel, and the lower value of Width leads to enhancement [8]. It also observed that a shift of Threshold Voltage exists while changing the dimensions.…”
Section: Optimization Directionmentioning
confidence: 96%
“…Come back with how CMOS works properly, we can find two ways to improve the efficiency, one is about material, and the other one is about Width Length ratio (W/L). According to the research, the way to improve CMOS performance is about the W/L, which can also be changed with applying different material [8]. In the paper, it demonstrates the Si-only interface together with SiGe interface.…”
Section: Optimization Directionmentioning
confidence: 99%
“…The present study provides a basis for channel width-to-length (W/L) ratio comparison, which indicates that the dominance of longitudinal or transverse configuration depends on this ratio. Moreover, this ratio may explain the reason that strained long SiGe p-channels are enhanced more than short p-channels are [6]. The mobility of long p-channels is enhanced because the piezoresistance coefficient of the longitudinal [1 1 0] p-channel is positive [7], and a relatively long channel has longitudinal dominance.…”
Section: Introductionmentioning
confidence: 99%
“…The long channels are not well defined, although they are valid from 10 m to tens of nanometer [1]- [3]. A recent report provided a basis for comparison using the channel width-to-length (W/L) ratio, which indicates that dominance of the longitudinal or transverse configurations depends on this ratio; moreover, this ratio may explain the underlying mechanism that causes the strained long SiGe p-channels to be enhanced more than the short p-channel [4]. Given that the piezoresistance coefficient of the longitudinal [110] p-channel is positive [5] and that the relatively long channel has longitudinal dominance, the mobility is enhanced.…”
mentioning
confidence: 99%